Penerapan Diversi Terhadap Anak Pelaku Tindak Pidana Narkotika Di Polsek Sunggal - Daniel Marunduri; Syafruddin Kalo; Madiasa Ablisar; Marlina Marlina (USU LAW JOURNAL, 2019)
Abstract : According to Article 82 of the Criminal Justice System for Children Act, the child of the offender may be given an action sanction by the judge. In this study, child perpetrators of narcotics crimes charged by the Public Prosecutor with criminal over 7 years imprisonment, was sanctioned action through a diversion attempt by the judge of the Medan District Court. Judge in making this decision using restorative justice approach to the child with legal instrument that is Regulation of The Supreme Court RI No. 4 of 2014 on the Guidelines for the Implementation of the Criminal Justice System for Children Act Diversity, this is contradictary to Article 7 paragraph (2) of the the Criminal Justice System for Children Act, because children who are threatened with imprisonment for 7 years can not be diversified, hierarchically in the legislation, the judge's action is contradictary to Article 7 Law No. 12 Year 2011 on the Establishment of Laws and Regulations. Supposedly, if the judge and the Prosecutor want to apply action sanction, can use the instrument of Article 82 paragraph (3) of the Criminal Justice System for Children Act, considering the legal threat of narcotics crime there is no mention of criminal at least 7 years imprisonment. In principle, the application of action sanctions against children as a form of child protection and can be as an effort to overcome the narcotics crime in children, since children are more likely as victims of crime.   Keywords : child perpetrators, narcotics crimes; and prevention.